Translation and validation of core bereavement items into Urdu language on a sample of bereaved parents and spouses in Pakistan - pilot study - Syed Aziz Uddin Agha; Mohammad Anis-Ul-Haque (Journal of the Pakistan Medical Association, 2021)
Abstract Core Bereavement Items Scale was translated into Urdu language and validated in Pakistani population through forward-backward procedure. It is 17-item scale with three subscales namely Images and thoughts; Acute Separation; and Grief. It was cross-sectional study commenced on 10th of June, 2016 and completed by July, 2017 as part of pilot study of PhD research at National Institute of Psychology, Quaid-I-Azam University, Islamabad. Sample of 260 participants was selected through a combination of convenience and snowball techniques. Results showed good alpha reliability and Item-total correlation ranged from 0.62 to 0.77. Confirmatory factor analysis showed good fit of the model on the data. Findings supported the three factor solution. The findings also indicated that female gender and people living in nuclear family system report more severe bereavement. Continuous...